Electronic formation of a contract - Kežmah, Urška (Informatica (Ljubljana), 2001)
This paper analysis main legal problems that are related to formation of e-contracts. Because of the different legal consequences it is highly important for parties to be aware and understand the basic phases of contract formation process. For a contract to exist, usually one party must have made offer, and the other must have accepted it. Once acceptance takes effect, a contract will usually be binding on both parties. A variety of procedures are available for forming an electronic contract, such as e-mail, EDI etc. Therefore, we have established that an electronic communication could create alegally binding contract. Business and other contracting parties should define and articulate most of the rules that will govern electronic commerce. Internationally, UNCITRAL Model law establishers rules and norms that validate and recognize contracts formed through electronic means, sets default rules for contract formation and governance of electronic contract performance.
Keywords: elektronska trgovina; elektronsko poslovanje; ponudba; naročilo